Efeitos da esplenectomia na homeostase de órgãos e sítios linfóides em camundongos BALB/c - Magda Luciana de Paula Rosa (2010)
The spleen acts as a filter, as it removes the blood cells and micro-organisms and cells covered by antibodies in physiological or pathological conditions. For its location and anatomy, the spleen is the main organ involved in early immune responses to blood-borne antigens. Despite the fact that removal of the spleen is associated with risk of subsequent infection, recommendation for total splenectomy still exists as a therapeutic aid for certain conditions. However, the impact of spleen removal on other lymphoid organs has been poorly evaluated. Herein we evaluate how the immune system reorganize its components in the absence of the spleen by studying the splenectomy in various lymphoid organs and sites 30 days thereafter. Spleen removal affected the immune system as a whole. There was no increase in the number of lymphocytes, either in blood or in the sum of the evaluated organs in splenectomized (SP) mice. However, when organs and sites were analyzed individually, changes in the number of lymphocytes were noticed in bone marrow (BM), thymus, mesenteric lymph nodes (MLn) and peritoneal cavity (PC). Migration studies of injected lymphocytes in SP mice showed a trend of TCD4+ and TCD8+ towards BM. B lymphocytes were more widely spread to other organs. The number of cells expressing activation molecules was also changed in SP mice: we observed a decrease in the number of activated B1a and B2 cells in PC, and an increase in activated B2 cells in BM. Moreover, SP mice showed reduced levels of IgA, IgM and IgG, IgG2b and IgG3. SP mice showed altered basal levels of cytokines in tissue extracts of BM, thymus and MLn. In general, SP mice produced low levels of IL-4, IL-10 and TGF-. However, MLn cells of these mice showed a higher production of IFN-. Finally, the number of antibody-producing cells in BM, thymus and MLn were also altered in SP mice. Our hypothesis is that some of these changes can be interpreted as compensatory mechanisms needed for adapting to the disturbances caused by the absence of the spleen. Adaptation does occur since splenectomized mice survive and are able to activate several types of immune responses.